2021
DOI: 10.1017/bpp.2020.60
|View full text |Cite
|
Sign up to set email alerts
|

Active inoculation boosts attitudinal resistance against extremist persuasion techniques: a novel approach towards the prevention of violent extremism

Abstract: The Internet is gaining relevance as a platform where extremist organizations seek to recruit new members. For this preregistered study, we developed and tested a novel online game, Radicalise, which aims to combat the effectiveness of online recruitment strategies used by extremist organizations, based on the principles of active psychological inoculation. The game “inoculates” players by exposing them to severely weakened doses of the key techniques and methods used to recruit and radicalize individuals via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Across two large-sample studies using different research designs, we find strong support that both active and passive prebunking interventions increase people’s ability to spot misinformation about COVID-19 in social media content. Additionally, in line with previous studies (Basol et al., 2020; Saleh et al., 2021), we find that prebunking interventions increase people’s confidence in their ability to spot misinformation. Crucially, this increase is in the right direction, so that people only became more confident in their ability when they correctly rated misinformation as manipulative.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Across two large-sample studies using different research designs, we find strong support that both active and passive prebunking interventions increase people’s ability to spot misinformation about COVID-19 in social media content. Additionally, in line with previous studies (Basol et al., 2020; Saleh et al., 2021), we find that prebunking interventions increase people’s confidence in their ability to spot misinformation. Crucially, this increase is in the right direction, so that people only became more confident in their ability when they correctly rated misinformation as manipulative.…”
Section: Discussionsupporting
confidence: 92%
“…At the start of the game, players were asked to participate in a scientific study. Consenting participants were shown three misinformation and three real news social media posts (in the form of Tweets) relating to COVID-19, and asked to rate the manipulativeness of each post on a 1-7 Likert scale (1 being 'not at all' and 7 being 'very', following Saleh et al, 2021). After completing the game, players were asked to participate in the second part of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who watched a brief training video that explained rhetorical techniques used by extremists were less likely to endorse subsequent radicalizing videos than people in the control condition who received no training. Similarly, in a recent study, Saleh et al (2021) found that participants who were exposed to weakened doses of the strategies used in extremist recruitment-as part of the interactive inoculation game Radicalize-were more resistant and better able to identify manipulative social media messages when compared to a control condition.…”
Section: Into the Rabbit Hole And Beyondmentioning
confidence: 81%
“…Although much is known about the effectiveness of inoculation against general misinformation (Cook et al, 2017 ; Roozenbeek & Linden, 2019 ; Roozenbeek et al, 2020 ; van der Linden et al, 2017a , 2017b ), the evidence base relating to extremism is scarce. In addition to the study by Braddock ( 2019 ) mentioned earlier, we know of only one further study (Saleh et al, 2020 ). This recent study inoculated participants through an “active” manipulation, by inviting participants to play a game in which they pretended to be a recruiter for a fictitious terrorist group.…”
Section: Discussionmentioning
confidence: 99%